If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3r=-6r+9
We move all terms to the left:
-3r-(-6r+9)=0
We get rid of parentheses
-3r+6r-9=0
We add all the numbers together, and all the variables
3r-9=0
We move all terms containing r to the left, all other terms to the right
3r=9
r=9/3
r=3
| 6=1/2z;z | | 9a+5=5a+49 | | w+6=2(-6) | | x+6(3)=-11 | | 6+3(6x-7)=9x+-15 | | 2(2x+1)=38, | | 31=5(u+7)-7u | | (x^2+1x)=2 | | 8t+2=8(4) | | 6+3(6x-7)=18x+-15 | | 164=50+4h+8h | | -35a=-20 | | 8t+2=8(4)+2 | | 7+2c=5+3c | | 8t+2=8 | | k*3=27 | | 1000–700=15x | | 75.11-23.96=x | | 0.50(6g+2)=12 | | 1/4x-4=3/7x+6 | | x*x*7=30 | | 45+21+8x=180 | | X^2+x*10^-8+10^-14=0 | | 15k-~5k+~18k=~20 | | X+5x-266=0 | | 10x-38=38+x+14 | | 7(z-4)=-28 | | 4k+28=-60 | | 18=x/4+7= | | 1/4k-4=3/7k+6 | | Y=-7-2x+11 | | 2^n=20000 |